Long‐term changes of polar mesosphere summer echoes at 69°N. Issue 18 (20th September 2013) - Latteck, R.; Bremer, J.
<x xml:space="preserve">Abstract</x> [1] Polar mesosphere summer echoes (PMSE) are strong enhancements of received signal power at very high radar frequencies occurring at altitudes between about 80 and 95km at polar latitudes during summer. PMSE are caused by inhomogeneities in the electron density of the radar Bragg scale within the plasma of the cold summer mesopause region in the presence of negatively charged ice particles. Thus, the occurrence of PMSE contains information about mesospheric temperature and water vapor content but also depends on the ionization due to solar electromagnetic radiation and precipitating high energetic particles. Continuous and homogeneous observations of PMSE have been done on the North‐Norwegian Island Andøya (69.3°N, 16.0°E) from 1994 until 2008 using the ALOMAR SOUSY and the ALWIN radar at 53.5MHz. In 2009, the Leibniz‐Institute of Atmospheric Physics in Kühlungsborn, Germany started the installation of the Middle Atmosphere ALOMAR Radar System (MAARSY) at the same location. The observation of mesospheric echoes could be continued in spring 2010 starting with an initial stage of expansion of MAARSY and is carried out with the completed installation of the radar since May 2011. Since both the ALWIN radar and MAARSY are calibrated, the received echo strength of PMSE from 14 years of mesospheric observations (1999–2012) could be converted into absolute signal power. This data series could be extended to the years 1994 until 1997 on the basis of signal‐to‐noise ratio values derived during the years between 1994 and 2008. The PMSE occurrence rate is positively correlated with the geomagnetic Ap index (significance level χ=85−95%), however, is not correlated with the solar Lyman α radiation. Using different regression analysis methods, the PMSE occurrence rates show a significant positive trend during the time interval from 1994 until 2012 (χ=95−99%).